Relationship between Family Income and Access to Primary Care of Senior Citizens in Kaytapos, Indang Cavite - Jayson Savilla; Ma. Angeline Maiza Quezon; Rhianne Kieth Sanchez; Mary Marie Lou Dequito; Danilo Carizo Jr (Journal of Social Responsibility, Tourism and Hospitality, 2024)
The research investigates the relationship between family income and access to primary care among senior citizens in Kaytapos, Indang Cavite. A combined self-administered survey and an in-person interview was conducted to analyze the multifaceted factors shaping the accessibility of primary care for seniors. The study examined the socio-economic status, health conditions, and the extent of their access to primary healthcare services. The study mainly aimed to assess the relationship between family income and access to primary care of senior citizens in Kaytapos, Indang. This study further seeks to identify the respondents’ socio-demographic profile and determine senior citizens’ access to primary care in terms of awareness, accessibility, affordability, availability, acceptability, and accommodation. Based on the findings, it was revealed that senior citizens have good access and high awareness of primary care. The affordability and accessibility of related goods and services were also moderate. Additionally, primary care providers and healthcare institutions were deemed moderately accessible, very acceptable, and highly accommodating to senior patients. Moreover, the existing relationship between family income and senior citizens’ access to primary care was statistically significant, yet there was a weak positive correlation. Hence, these findings could aid the government in policy-making planning to promote a more equitable and inclusive healthcare system. Overall, it was recommended that the government address the insufficient access to primary care by proposing free monthly check-ups, medicines, food, and allowances, especially for senior citizens in the lower income bracket.